Respiratory flexibility and efficiency are affected by simulated global change in Arctic plants. Issue 4 (21st December 2012) - Kornfeld, Ari; Heskel, Mary; Atkin, Owen K.; Gough, Laura; Griffin, Kevin L.; Horton, Travis W.; Turnbull, Matthew H.
Summary: Laboratory studies indicate that, in response to environmental conditions, plants modulate respiratory electron partitioning between the 'energy‐wasteful' alternative pathway (AP) and the 'energy‐conserving' cytochrome pathway (CP). Field data, however, are scarce. Here we investigate how 20‐yr field manipulations simulating global change affected electron partitioning in Alaskan Arctic tundra species. We sampled leaves from three dominant tundra species – Betula nana, Eriophorum vaginatum and Rubus chamaemorus – that had been strongly affected by manipulations of soil nutrients, light availability, and warming. We measured foliar dark respiration, in‐vivo electron partitioning and alternative oxidase/cytochrome c oxidase concentrations in addition to leaf traits and mitochondrial ultrastructure. Changes in leaf traits and ultrastructure were similar across species. Respiration at 20°C ( R 20 ) was reduced 15% in all three species grown at elevated temperature, suggesting thermal acclimation of respiration. In Betula, the species with the largest growth response to added nutrients, CP activity increased from 9.4 ± 0.8 to 16.6 ± 1.6 nmol O2  g −1 DM s −1 whereas AP activity was unchanged. The ability of Betula to selectively increase CP activity in response to the environment may contribute to its overall ecological success by increasing respiratory energy efficiency, and thus retaining more carbon for growth.